Theoretical interdisciplinary approaches in the work of the National University of Costa Rica with children and adolescents: contributions from the institutional trajectory - Chaverri Chaves, Pablo (2023)
This paper consists of a reflective essay on conceptual approaches that the National University (UNA) of Costa Rica has been using in the understanding and work with and on minors from different fields and areas of knowledge. This research addresses eleven different approaches, namely: historical, integral human development, human rights, public policies, literary, gender, human movement, life cycle, beliefs, new humanism, and culture of peace. In each case, the approach in question is described, it explains why it is socially important, and why it is fundamental for universities to consider it in their work of social commitment with children and adolescents. The essay closes with a concluding section that integrates the various approaches addressed and proposes some implications of such approaches for university work, broadly understood, oriented towards minors.